Effect of sustained inflation duration; resuscitation of near-term asphyxiated lambs - Klingenberg, Claus; Sobotka, Kristina S; Ong, Tracey; Allison, Beth J; Schmölzer, Georg M; Moss, Timothy J M; Polglase, Graeme R; Dawson, Jennifer A; Davis, Peter G; Hooper, Stuart B (Archives of disease in childhood. Fetal and neonatal edition, 2013)
Objective The 2010 ILCOR neonatal resuscitation guidelines do not specify appropriate inflation times for the initial lung inflations in apnoeic newborn infants. The authors compared three ventilation strategies immediately after delivery in asphyxiated newborn lambs. Design Experimental animal study. Setting Facility for animal research. Subjects Eighteen near-term lambs (weight 3.5–3.9 kg) delivered by caesarean section. Interventions Asphyxia was induced by occluding the umbilical cord and delaying ventilation onset (10–11 min) until mean carotid blood pressure (CBP) was ≤22 mm Hg. Animals were divided into three groups (n=6) and ventilation started with: (1) inflation times of 0.5 s at a ventilation rate 60/min, (2) five 3 s inflations or (3) a single 30 s inflation. Subsequent ventilation used inflations at 0.5 s at 60/min for all groups. Main outcome measures Times to reach a heart rate (HR) of 120 bpm and a mean CBP of 40 mm Hg. Secondary outcome was change in lung compliance. Results Median time to reach HR 120 bpm and mean CBP 40 mm Hg was significantly shorter in the single 30 s inflation group (8 s and 74 s) versus the 5×3 s inflation group (38 s and 466 s) and the conventional ventilation group (64 s and 264 s). Lung compliance was significantly better in the single 30 s inflation group. Conclusion A single sustained inflation of 30 s immediately after birth improved speed of circulatory recovery and lung compliance in near-term asphyxiated lambs. This approach for neonatal resuscitation merits further investigation.